2014
DOI: 10.4238/2014.may.9.17
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effects of proteasome and histone deacetylase inhibitors in prostate cancer cell lines

Abstract: ABSTRACT. Prostate cancer is one of the most common types of urological cancers. Despite the implementation of effective radiotherapy and chemotherapy methods, prostate cancer cells can still show resistance to treatment. In recent years, a combination of proteasome and histone deacetylase inhibitors has been used to treat various malignancies. In this study, we examined the cytotoxic and apoptotic effects of the proteasome inhibitor bortezomib (Velcade/PS-341) and histone deacetylase inhibitor trichostatin A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…The proteasome inhibitor bortezomib selectively targets the catalytic B-subunits of the proteasome, inhibiting the chymotrypsin-like and to a lesser degree the caspase-like activity (63). Inhibition of the 26S proteasome prevents IkBα degradation, thereby blocking NF-κB nuclear translocation (66, 67), although it is unclear that this is the primary anti-cancer mode of action.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome inhibitor bortezomib selectively targets the catalytic B-subunits of the proteasome, inhibiting the chymotrypsin-like and to a lesser degree the caspase-like activity (63). Inhibition of the 26S proteasome prevents IkBα degradation, thereby blocking NF-κB nuclear translocation (66, 67), although it is unclear that this is the primary anti-cancer mode of action.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…The moderate efficacy demonstrated in preclinical animal models for solid tumors has typically been associated with the inhibition of NF-κB and of NF-κB-dependent gene expression (5, 66, 68). Unfortunately, single-agent bortezomib treatment was ineffective in treating unresectable gastric adenocarcinoma in a phase II multicenter trial (69).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…We found that proliferation of all three cell lines were inhibited by low concentrations of bortezomib, with similar IC50s of 4.26 nM for PC3, 7.59 nM for LNCaP and 2.41 nM for VCAP, which are consistent with previously reported results. 27,28 All of these cell lines were derived from patients age o65 (PC3: 62 years old, 29 LNCaP: 50 years old 30 and VCAP: 59 years old 31 ). To our knowledge, there are no PCa cell lines available from older patients.…”
Section: Demographicsmentioning
confidence: 99%
“…This result is in agreement with a number of previous studies performed on prostate cancer cells. For instance, Kiliccioglu et al (18) determined the IC 50 value of bortezomib to be 30 nM, following 24-h treatment in LNCaP cells (bearing wild-type p53), and 50 nM in PC-3 cells (which are p53-deficient). By contrast, Williams et al (19) indicated that the IC 50 value of bortezomib was ~10 nM following 48 h of treatment in PC-3 cells.…”
Section: Discussionmentioning
confidence: 99%